2011
DOI: 10.1051/0004-6361/201116451
|View full text |Cite
|
Sign up to set email alerts
|

Gravity and limb-darkening coefficients for theKepler, CoRoT,Spitzer,uvby,UBVRIJHK, and Sloan photometric systems

Abstract: Aims. The complex physics of close binary stars is made even more challenging by the proximity effects that affect it. Understanding the influence of these proximity effects is one of the most important tasks in theoretical stellar astrophysics. It is crucial to know how the specific intensity is distributed over the stellar disk for a correct modelling of the light curves of eclipsing binaries and planetary transits. To provide theoretical input for light curve modelling codes, we present new calculations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
1,088
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,088 publications
(1,127 citation statements)
references
References 13 publications
34
1,088
5
Order By: Relevance
“…We adopt the analytic model of Mandel & Agol (2002) for the transit profile, with quadratic limb-darkening parameters from Claret & Bloemen (2011). Atmospheric parameters come from the most recent version of the Kepler Input Catalog retrieval from the NASA Exoplanet Archive (Huber et al 2014).…”
Section: Stellar Parametersmentioning
confidence: 99%
“…We adopt the analytic model of Mandel & Agol (2002) for the transit profile, with quadratic limb-darkening parameters from Claret & Bloemen (2011). Atmospheric parameters come from the most recent version of the Kepler Input Catalog retrieval from the NASA Exoplanet Archive (Huber et al 2014).…”
Section: Stellar Parametersmentioning
confidence: 99%
“…In a first MCMC run, we keep the eccentricity fixed to zero as previous studies using radial-velocity data, which provides better constraints on √ e sin ω, found eccentricity values consistent with 0 (Nelson et al 2014). We also add the limbdarkening linear combinations c1 = 2u1 + u2 and c2 = u1 − 2u2 as jump parameters, where u1 and u2 are the quadratic coefficients drawn from the theoretical tables of Claret & Bloemen (2011) using published stellar parameters (von Braun et al 2011). We impose Gaussian priors on the limb-darkening coefficients and the radial-velocity semi amplitude K (Nelson et al 2014).…”
Section: Refinement Of the System Parametersmentioning
confidence: 99%
“…The a/R * , e, ω, i, and P p of each of the planets are fixed to their values listed in Table 6. The linear and quadratic limb darkening coefficients in each filter are taken from Claret & Bloemen (2011) and interpolated to the stellar parameters of the host stars (see Table 7) using the EXOFAST applet 8 (Eastman et al 2013). In addition, a linear or quadratic least squares fit is modelled to the OoT baseline simultaneously with the Mandel & Agol (2002) model.…”
Section: Exomop Analysis Of the Systemsmentioning
confidence: 99%